Cdh13 and AdipoQ gene knockout alter instrumental and Pavlovian drug conditioning. (2nd May 2017) - King, C. P.; Militello, L.; Hart, A.; St. Pierre, C. L.; Leung, E.; Versaggi, C. L.; Roberson, N.; Catlin, J.; Palmer, A. A.; Richards, J. B.; Meyer, P. J.
Abstract : Genome‐wide association studies in humans have suggested that variants of the cadherin‐13 ( CDH13 ) gene are associated with substance use disorder, subjective response to amphetamine, and attention deficit hyperactivity disorder. To examine the role of the Cdh13 and its peptide ligand adiponectin ( AdipoQ ) in addiction‐related behaviors, we assessed Cdh13 knockout (KO) rats and AdipoQ KO mice using intravenous cocaine self‐administration and conditioned place preference (CPP) paradigms. During intravenous cocaine self‐administration, male Cdh13 heterozygous (+/−) and KO (−/−) rats showed increased cue‐induced reinstatement compared with wild‐type (WT) rats when presented with a cocaine‐paired stimulus, whereas female Cdh13 rats showed no differences across genotype. Cdh13 −/− rats showed higher responding for a saccharin reinforcer and learned the choice reaction time (RT) task more slowly than WTs. However, we found no differences between Cdh13 −/− and +/+ rats in responding for sensory reinforcement, number of premature responses in the RT task, tendency to approach a Pavlovian food cue, CPP and locomotor activation to cocaine (10 or 20 mg/kg). In AdipoQ −/− mice, there was a significant increase in CPP to methamphetamine (1 mg/kg) but not to a range of d‐amphetamine doses (0.5, 1, 2 and 4 mg/kg). Taken together, these data suggest that Cdh13 and AdipoQ regulate sensitivity to psychomotor stimulants and palatable rewards without producing major changes in other behaviors. In humans, these two genes may regulate sensitivity to natural and drug rewards, thus influencing susceptibility to the conditioned drug effects and relapse. Abstract : Cue‐induced reinstatement to cocaine is increased in male Cdh13 knockout and heterozygous rats.